Conocimiento y uso de herramientas informáticas en docentes de instituciones educativas de la zona rural, Loreto 2025 - Marin Laulate, Rosario (2025)
The study, whose objective was to determine the relationship between knowledge and use of computer tools among teachers at educational institutions in rural areas of the Loreto region in 2025, was developed using a quantitative approach, with a basic type, a non-experimental design, and a correlational level. The population consisted of 114 teachers, selected through census sampling. A Likert-type questionnaire was applied, validated by expert judgment and with high reliability (Cronbach's α > 0.940). The results showed that 64.9% of teachers have a low level of technological knowledge, while 93.9% show medium and high levels of use of computer tools, using them mainly for administrative rather than pedagogical purposes. Spearman's Rho correlation test determined that there is no significant relationship between knowledge and use of computer tools p-valor = 0,816 > α = 0,05 y Rho Spearman's = 0,022, so the general hypothesis was rejected. Similarly, no significant relationships were found between the dimensions of the knowledge variable (acquisition, depth, creation, and professional learning) and the use of IT tools in teaching practice. It is concluded that the technological knowledge acquired by rural teachers does not translate into effective pedagogical integration due to structural limitations such as insufficient connectivity, lack of contextualized training, and a weak institutional digital culture.